Quality Improvement Using the Six Sigma DMEDI Method for Hand Sterilizer Products - Yojana, Ratna Mira Yojana; Clarresta , Cynthia Clarresta; Fitiana, Rina Fitiana (JURNAL TEKNIK INDUSTRI, 2025)
XC Clenaindo Company is a manufacturing company that provides cleaning and sanitation services in Indonesia. However, defects that exceeded the company's tolerance limits were found in hand sterilizer products. This research aims to improve product quality so that it satisfies customer needs. Analysis was conducted to determine the leading causes of product defects using the Six Sigma Define, Measure, Explore, Design, and Implement (DMEDI) method. The DMEDI Six Sigma method is a quality improvement method with a creative approach so that the resulting solution can be a new work system design. The results of the defined process research found two problems, namely product defects because the Sterobac hand sterilizer bottle was convex and the length of the label installation process. At the measure stage, it was discovered that the problem was in the filling and labeling process, which was influenced by the increasing number of requests. At the exploration stage using the 5 why deep interview method, it was discovered that the problem was due to the lack of temperature during the liquid pouring process and the label design making the sticking process difficult. So, the work process was redesigned at the filling stage, and a new label design was created, which made it easier for workers to stick labels and apply the 5S concept. The final stage was implemented by designing the Poka-Yoke Form and Worker Operational Standards for the Filling. This research results in a reduction in the number of defective products.